Diagnostic accuracy of magnetic resonance imaging in detecting the severity of abnormal invasive placenta: a systematic review and meta‐analysis. (13th December 2017) - Familiari, Alessandra; Liberati, Marco; Lim, Philip; Pagani, Giorgio; Cali, Giuseppe; Buca, Danilo; Manzoli, Lamberto; Flacco, Maria E.; Scambia, Giovanni; D'antonio, Francesco
Abstract: Introduction: Accurate prenatal diagnosis of abnormally invasive placenta (AIP) is fundamental because it significantly reduces maternal morbidities. Material and methods: Medline, Embase, CINAHL and the Cochrane databases were searched. The primary aim of the present review was to elucidate the diagnostic accuracy of prenatal magnetic resonance imaging (MRI) in recognizing the severity of AIP, defined as the depth and topography of invasion. The secondary aim was to ascertain the strength of association between each MRI sign and the depth of placental invasion and to test their individual predictive accuracy in detecting such invasion. Inclusion criteria were studies on women who had prenatal MRI for ultrasound suspicion or the presence of clinical risk factors for AIP. Estimates of sensitivity, specificity, positive and negative likelihood ratios and diagnostic odds ratio were calculated using the hierarchical summary receiver characteristics curve model, and individual data random‐effect logistic regression was used to calculate OR. Results: Twenty studies (1080 pregnancies undergoing MRI mainly for the ultrasound suspicion of AIP) were included. MRI showed a sensitivity of 94.4% [95% confidence interval (CI) 15.8–99.9], 100% (95% CI 75.3–100) and 86.5% (95% CI 74.2–94.4) for detection of placenta accreta, increta and percreta, respectively; the corresponding values for specificity were 98.8% (95% CI 70.7–100), 97.3% (95% CI 93.3–99.3), 96.8% (95% CI 93.5–98.7). MRI identified 100% of cases with S1 and 100% of those with S2 invasion confirmed at surgery. Among the different MRI signs, intra‐placental dark bands showed the best sensitivity for the detection of placenta accreta, increta and percreta; as well as abnormal intra‐placental vascularity, uterine bulging was associated with a higher risk of increta and percreta, exophitic mass and bladder tenting with placenta percreta. Conclusion: Prenatal MRI has an excellent diagnostic accuracy in identifying the depth and the topography of placental invasion. However, these findings come mainly from studies in which MRI was performed as a secondary imaging tool in women already screened for AIP on ultrasound and might not reflect its actual diagnostic performance in detecting the severity of these disorders.